Chemical oxygen demand removal using artificially constructed biofilm by dielectrophoresis on wirecloth electrode - Wai, York Chow (2014)
Artificial structured biofilm constructed (ASB) by dielectrophoresis (DEP) principle using wirecloth electrode was explored for its potential in wastewater treatment. The wirecloth produced by adopting textile technology, utilised 100 μm stainless steel wire and 83 decitex polyester yarns. The wirecloth is highly flexible and able to be fixed in most treatment system. The ASB was then immobilized using polyethylenimine (PEI) solution. The biofilm formation time was greatly shortened as the DEP attraction can result in an effective immobilization process. Micrococcus sp., Rhodococcus sp. and Bacillus sp. isolated from pharmaceutical wastewater was used. A lab scale reactor was used to determine the optimum conditions and the ability of DEP-constructed biofilm in wastewater treatment. The experiment parameters included wirecloth surface area, pH, temperature and HRT. 2 types of medium; low strength and high strength synthetic wastewater were used in the experiments. The treatment process showed a good potential in treating both type of synthetic wastewater where almost 90% COD reduction was achieved at the optimum conditions for each parameter. The larger the wirecloth surface area used the better the COD reduction can be achieved. The restriction may only cause by insufficient of nutrient in a given medium’s volume. The performance of the artificial biofilm was dependent on the pH value. The optimum pH value for both mediums was found to be pH 8. Lower pH and higher pH value tend to inhibit the activity of microorganisms and decrease the COD reduction to 62.4% in low strength and 75.1% in high strength synthetic wastewater, respectively. The best temperature chosen was 40°C. This is due to higher COD removal rate achieved and the COD reduction was nearly 90% for both mediums. The suitable HRT for low strength synthetic wastewater are around 1 to 3 days and the HRT for high strength synthetic wastewater was 4 to 7 days. As the COD value was higher, shorter retention time will result in an incomplete treatment where COD reduction was just 56.3%. The built up of artificial biofilm (increase of active biomass) can eventually shorten the treatment time which shown in the experiment results of HRT. ESEM and SEM images revealed the surface morphology of ASB. The layers of EPS proved to be interconnected and support the nutrient diffussion and the build up of microcolonies for a better COD removal.